Study of Di-Muon Production Process in pp Collision in CMS Data from Symmetry Scaling Perspective - Susmita Bhaduri; Anirban Bhaduri; Dipak Ghosh (Advances in High Energy Physics)
An extensive knowledge of the dynamics of the process of pp collision serves as input to exhaustive theoretical models of strong interaction. This knowledge is also a baseline for a system to decipher the dynamics of AA collisions at relativistic and ultrarelativistic energies. Recent availability of di-muon data has triggered a spate of interests in revisiting strong interaction process, the study of which in detail is extremely important for enhancement of our understanding of not only the theory of strong interaction but also possible physics scenarios beyond the standard model. Apart from conventional approaches to the study of the dynamics of particle production in high-energy collision the present authors proposed a new approach with successful application in context of symmetry scaling in AA collision data from (ALICE-Collaboration, 2014) in the work (Bhaduri, S. et al., 2019) and pp collision data at 8TeV from (CMS-collaboration, 2017) in the work (Bhaduri, S. et al., 2019) and also in other numerous works with different collision data. This different approach essentially analyses fluctuation pattern from the perspective of symmetry scaling or degree of self-similarity involved in the process. This was done with the help of multifractal scaling analysis and also multifractal cross-correlation analysis using the single variable of pseudorapidity values of di-muon data taken out from the primary dataset of RunA(2011) and RunB(2012) of the pp collision at 7 TeV and 8 TeV, respectively, from (CMS-collaboration, 2016, 2017). High degree of persistent long-range cross-correlations (MF-DXA) exist between pseudorapidity-value and its corresponding azimuthal-value for different rapidity ranges. The different values of scaling exponents (across rapidity ranges and energies) signify that there may be multiple processes other than those conjectured, involved in the underlying dynamics of the production process of oppositely charged di-muons resulting in different kinds of scaling. Otherwise, the scaling exponents at different degrees would have remained the same across the rapidity ranges and also for different energies.